Landscape Optimal Suitability Analysis Method: The Case of Anamur District - Erbesler Ayasligil, Tulay (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2020)
Due to the increasing population and life-needs both in the world and in Turkey, most appropriate use of natural resources should be determined. Sustainable development depends on taking the right land use decisions. Productivity of soil structure determines biomass performance of that field. This study aims to determine optimal ways of using Anamur land according to three kinds of land use: agricultural, forest, meadows-ranges. Geographic Information Systems (GIS) assisted Landscape Optimal Suitability Analysis Method (LANDEP) was used in the study. In this scope, absolute evaluation parameters were determined through the review of 27 studies from the literature. These parameters are topography (altitude, slope), soil characteristics (large soil groups, land usability groups), soil restriction factors (erosion, salinity, drainage, stoniness, wetness, soil depth), climactic features (exposure, temperature, precipitation), geomorphological structure, current land use status. Sub-criteria, standards and significance of these criteria were determined in line with the current research and their suitability were evaluated according to type of land use. Lands were classified as suitable and unsuitable lands and 'Agricultural, Forest and Meadow-Range Landscape Suitability Maps were generated through grading. When the research area was evaluated in terms of suitability (1st, 2nd and 3rd grade), 46% are suitable for agriculture, 96% are suitable for forest and 5% are suitable for meadow and range. Primary land use type in terms of production capacity were determined with suitability comparison and suggestions were offered by creating Combined Suitability Map.
Keywords: Analytical hierarchy process; meadow-range; geographic information system; multi-criteria decision-making model; ecological planning; optimal suitability analysis; forest; agriculture; Architecture